(3GdehGgH hGdeff aj efGbH GdEeGe MSf Hf SjOfG Ydj Hf CHj WGdH hGHf GdSjOI GdHJhds - (3GdYdhqj GdTGaYqj GdLaQj, eMeO Hf MSjf, J (B1186 (3g`s ((3jhSa Hf eMeO MeGOs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3ef CUHMhG hge CYdi GdhQi fSHG hSGQ UjJge aj GdfGS cGdeKdj (B*** (3hcja dG hge Ef jfSHhG GJUdJ CfSGHge HGdfHj hGdEeGe Ydj (B...s
(3BNQgG (B:s
... (3hUdi Ydjg SYjO Hf GdYGU hcGf EP PGc CejQ GdeOjfI ef WQa eYGhjI bOeg GdMSjf hbGd gj GdSfI hOaf HYO GdUdGI Ydjg (B...(3hcGf GdaQGZs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\104s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJGQjNs